Triterpenoids isolated from helicteres hirsuta - Le , Dang Khoa; Hoang, Minh Hao (Journal of Technical Education Science, 2020)
Helicteres family widely distributed from southern China to India, Southeast Asia. There are seven species in Vietnam and described as traditional medicinal plants. The information about the chemical constituents of Helicteres hirsuta in Vietnam has not been fully reported. In present work, we presented the isolation and structural elucidation of four terpenoids (1-4) isolated from Helicteres hirsuta L. which collected from Binh Phuoc province. The powder of the leaves and stem were separately macerated in ethanol at room temperature. The ethanol solutions were removed solvent under reduced pressure to obtain the ethanolic extracts. The ethanolic extract was applied on the silica gel dried column and sequentially eluted with n-hexane, chloroform, ethyl acetate (EtOAc) and methanol. Basing on TLC results, the sub-extract residues were selected to isolate the pure compounds by using CC technique in combination with recrystallization technique. (1) was isolated from the chloroform residue of the stem ethanolic extract while (2) obtained from a sub-fraction by recrystallizing in a mixture of n-hexane/EtOAc (8:2). (3) was a white precipitate which obtained while eluting with EtOAc to the stem extract. The crude extract n-hexane from the leaf was separated by CC using n-hexane/EtOAc gradient elution to afford (4). Chemical structures of isolated compounds were elucidated by NMR and MS spectroscopies in comparison with the literature.